2015
DOI: 10.1155/2015/147909
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Potential in Different Parts and Callus ofGynura procumbensand Different Parts ofGynura bicolor

Abstract: Plants from Gynura family was used in this study, namely, Gynura procumbens and Gynura bicolor. Gynura procumbens is well known for its various medicinal properties such as antihyperglycaemic, antihyperlipidaemic, and antiulcerogenic; meanwhile, G. bicolor remains unexploited. Several nonenzymatic antioxidants methods were utilized to study the antioxidant capacity, which include ferric reducing antioxidant power (FRAP), 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, total flavonoid content, to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 25 publications
2
35
0
Order By: Relevance
“…The results follow the same pattern found in (AA%) suggesting a correlation between both responses that has been quoted in recent researches about higher AA% related with TP (Zimmer et al 2012;Ramkissoon et al 2013). Krishnan et al (2015) also reported for Gynura procumbens higher TP concentration in root callus than those values from other plant part callus (leaf with 0.483, stem with 0.559, and root with 0.891 mg GAE g −1 Fresh Weight).…”
Section: Total Phenols (Tp)supporting
confidence: 89%
“…The results follow the same pattern found in (AA%) suggesting a correlation between both responses that has been quoted in recent researches about higher AA% related with TP (Zimmer et al 2012;Ramkissoon et al 2013). Krishnan et al (2015) also reported for Gynura procumbens higher TP concentration in root callus than those values from other plant part callus (leaf with 0.483, stem with 0.559, and root with 0.891 mg GAE g −1 Fresh Weight).…”
Section: Total Phenols (Tp)supporting
confidence: 89%
“…In addition, the administration of methanol extract prior to oxidative stress induction was able to reverse the elevation of plasma lipid peroxidation in tested animals (Akowuah et al, 2012). In order to differentiate the antioxidative capacity of different parts of G. procumbens , a recent study was conducted by Krishnan et al (2015). The study revealed that the root extract showed the highest antioxidant activity when compared to the other parts of the plant.…”
Section: Biological Activitiesmentioning
confidence: 99%
“…In Malay, G. procumbens is called Sambung Nyawa which means “prolongation of life” whereas in Chinese, it is called Bai Bing Cao which means “100 ailments” (Bodeker et al, 2009). This is because it has been utilized in traditional medicine both systemically and for topical application for treatment of different types of illnesses and diseases (Krishnan et al, 2015). For example, it is widely used to relieve kidney discomfort in Indonesia and people have been using it for the treatment of fever in Vietnam.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the administration of methanol extract before oxidative stress induction was able to reverse the elevation of plasma lipid peroxidation in tested animals [51]. Krishnan et al [58] revealed that the root extract has the highest antioxidant activity when compared to the other parts of the plant.…”
Section: Antioxidant Activitymentioning
confidence: 99%